Pirh2 RING-finger E3 ubiquitin ligase: its role in tumorigenesis and cancer therapy - Jung, Yong-Sam (2012)
The ubiquitin-dependent proteasome system plays a critical role in many cellular processes and pathogenesis of various human diseases, including cancer. Although there are a large number of E3 ubiquitin ligases, the majority are RING-finger type E3s. Pirh2, a target of p53 transcription factor, contains a highly conserved C(3)H(2)C(3) type RING domain. Importantly, Pirh2 was found to regulate a group of key factors dedicated to the DNA damage response, such as p53, p73, PolH, and c-Myc. Interestingly, Pirh2 was upregulated or downregulated in different types of cancers. These suggest that Pirh2 is implicated in either promoting or suppressing tumor progression in a tissue-dependent manner. This review will focus on the major findings in these studies and discuss the potential to explore Pirh2 as a cancer therapeutic target.